oTree: The Equality Equivalence Test - Felix Holzmeister; Rudolf Kerschbamer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
Based on a small set of assumptions on preferences, Kerschbamer (2015) introduces a geometric delineation of distributional preferences and a parsimonious, non-parametric identification procedure - the Equality Equivalence Test (EET). The assumptions of the test result in a mutually exclusive taxonomy of social preference archetypes, nesting all empirically relevant types identified in the literature. This article presents a ready-to-use software module for use with oTree (Chen et al., 2016), which facilitates the implementation of the EET in the laboratory, the field, or online. The app can be straightforwardly configured and parametrized using a single file and can be seamlessly integrated into existing projects. Furthermore, the app features predefined evaluations of subjects' responses and provides a real-time report of the results in the experimenter's dashboard. By this means, the module offers a comprehensive, flexible, and time-saving tool for implementing and conducting the EET in a myriad of configurations determined by the user.
Keywords: C81; C90; D63; D91; 330; oTree; Equality Equivalence Test; Distributional Preferences